Review of animal behavioral ecology in tropical regions (Zoological Records and Reviews, 2024)
Tropical regions harbour the majority of Earth's terrestrial animal diversity and present a suite of ecological conditions --year-round resource availability, intense biotic interactions, and high structural complexity -- that have driven theevolution of behaviours absent or rare in temperate systems. This review synthesises findings from 187 empirical studiespublished between 2000 and 2024 on animal behavioural ecology in tropical regions, covering four thematic domains: (i)foraging behaviour and optimal diet theory under high prey diversity; (ii) social organisation and cooperative behaviour in the context of intense predation pressure; (iii) communication systems including visual, acoustic, and chemical signalling in structurally complex habitats; and (iv) behavioural responses to anthropogenic disturbance including deforestation, hunting, and climate warming. Meta-analysis of 64 studies on tropical foraging behaviour reveals that diet breadth is significantly narrower in tropical than in temperate congeners when controlling for body mass (Hedges' g = -0.71, 95% CI:-0.94 to -0.48), consistent with the specialist-generalist prediction of MacArthur and Wilson (1967) under high-diversity resource environments. Social group size scales positively with predator diversity across 38 primate and ungulate populations (r = 0.68, p < 0.001). Acoustic signal complexity correlates negatively with habitat openness across 29 passerine radiations (r = -0.74, p < 0.001), consistent with the acoustic adaptation hypothesis. Behavioural flexibility --quantified as intraspecific variation in foraging strategy and social organisation -- emerges as the primary predictor ofspecies persistence in disturbed tropical landscapes. We identify key research gaps and propose a unified framework forprioritising behavioural ecology studies in regions most threatened by accelerating land-use change.